The system of tumor necrosis factor α in the pathogenesis of autoimmune diabetes mellitus - T. S. Prokhorenko; T. V. Saprina; F. E. Lazarenko; N. V. Ryazantseva; I. N. Vorozhtsova; V. V. Novitsky (Бюллетень сибирской медицины)
The aim of this study was to evaluate the impact of TNFα and their receptor in autoimmune diabetes. It was found the most pronounced inhibition of production of soluble forms of the receptor for TNFα in the background of an increased number of lymphocytes bearing membrane-associated receptors for TNFα in patients with manifested variant of diabetes type 1, compared to patients with latent autoimmune diabetes of adults.